Evaluation of the quality of the media content of reports and financial statements published electronically in the Khartoum Stock Exchange from the perspective of investors - Mohamed, Fateh AlIlah Mohamed Ahmed; Ahmed, Mohamed Saad Obeid Mohamed (Journal of Economic, Administrative and Legal Sciences, 2017)
The study dealt with the electronic dissemination of information accounting in capital markets in developing countries, where the study aimed to assess the quality of the content of accounting information contained in the reports and the financial statements published electronically in Khartoum Securities Market from the point of view of investors through the statement of the availability of qualitative characteristics of accounting information, the degree of confidence of investors in the accounting information contained in the reports and the financial statements published electronically. To achieve those purposes a questionnaire has been prepared to collect data from investors in Khartoum Securities Market. The study sample consists of (90) investors. The main findings of the study are that: high availability of qualitative characteristics of accounting information in the reports and financial statement published electronically, and investors in Khartoum Securities Market have high confidence in content of accounting information disseminated electronically.